Climate Change and Human Psychology: A Comprehensive Analysis of Thoughts and Emotions - Brika, Said; Soltani, Hassen; Abderzag, Fouzi Tahar; Ghandri, Mohamed; Lamari, Iman Ahmed (Journal of Ecohumanism, 2024)
The paper aims to find out how changes in climate change affect how people think and feel. This paper analyzes 1456 papers published in WOS data from 1964 to 2022 that assessed the impact of climate change on knowledge, attitudes, behaviour, and policy preferences. We used a comprehensive search technique to identify and analyze the articles. VOSviewer, Bibliometrics, and Biblioshiny from R were used in the bibliometric study to reveal new research trends in climate change. The results show five sub-fields of research in this area (climate change, global warming, uncertainty and policy, human activities, land usage, and risk assessment). Other topics comprise the study of trends in this discipline, such as systems, design, snow, river basins, and change impacts. Our analysis indicates several gaps and problems in the climate change literature. There is, for example, a scarcity of studies on climate justice and the social and political components of climate change. Additionally, many studies focus on wealthy countries, leaving out the effects of climate change on vulnerable populations in developing countries. We find that the research areas for climate change trends in those publications give a complete perspective of the climate change research landscape, which may be used to drive future research agendas and policy decisions, etc. Lastly, we suggest different directions that climate change research could go in the future. These include more collaborations between different fields, a stronger focus on the social and political aspects of climate change, and a stronger focus on how climate change affects vulnerable groups.